2011
DOI: 10.1021/ja205714g
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene and Brønsted Acid Cooperative Catalysis: Asymmetric Synthesis of trans-γ-Lactams

Abstract: An efficient enantioselective approach to form trans-γ-lactams in up to 99% yield, 93% ee and >20/1 dr using unactivated imines has been developed. The cyclohexyl-substituted azolium and the weak base sodium o-chlorobenzoate are most suitable for this transformation. Notably, the process involves cooperative catalysis by N-heterocyclic carbene and Brønsted acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(103 citation statements)
references
References 65 publications
2
97
0
4
Order By: Relevance
“…This strong HFIP effect is intriguing. Rovis and co-workers 53,54 showed that less basic triazolium salt-derived NHC catalysts can co-exist with weak Brønsted acids (for example, carboxylic acids). A control experiment was carried out to test the benzoin condensation reaction using benzaldehyde under our standard conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This strong HFIP effect is intriguing. Rovis and co-workers 53,54 showed that less basic triazolium salt-derived NHC catalysts can co-exist with weak Brønsted acids (for example, carboxylic acids). A control experiment was carried out to test the benzoin condensation reaction using benzaldehyde under our standard conditions.…”
Section: Discussionmentioning
confidence: 99%
“…NHCs and acids play different catalytic roles in the reaction system. [39][40][41][42] These syntheses require the presence, in the reaction mixture, of both an NHC and an acid; this situation is possible only if the Brønsted acid is unable to protonate the NHC quantitatively (in spite of the significant basicity of the NHC).…”
Section: Stability Of Nhc: Role Of Acetic Acidmentioning
confidence: 99%
“…The Rovis group reported an NHC-Brønsted acid cooperative catalyzed reaction using cyclohexyl-substituted azolium and the weak base sodium o-chlorobenzoate, to generate asymmetric trans-g-lactams (Scheme 14). 24 Compounds 64 and 65 were treated with catalytic system (azolium and Scheme 13. Brønsted Acid-mediated Reaction of g-Lactams with Indoles.…”
Section: Brønsted Acid Cooperative Catalysismentioning
confidence: 99%